Chemical constituents from the roots of Actinidia valvata Dunn. (February 2022) - Song, Changwei; Yu, Chunbo; Qin, Ying; Hui, Jing; Zhang, Yong; Qian, Shengyan; Xu, Lin; Liu, Yun
Abstract: A previous undescribed dihydrobenzofuran neolignan (1 ), as well as eleven known phenolic derivatives (2 –12 ) were isolated from the n -butanol fraction of the roots of Actinidia valvata Dunn, including five phenylpropanoids (2 –6 ), four phenolic glycosides (7 –10 ) and two coumarins (11 –12 ). The chemical structures of these compounds were identified by means of extensive spectroscopic analysis and comparison with the previously reported data. Besides, the chemotaxonomic significance of these secondary metabolites was discussed. Graphical abstract: Image 1 Highlights: One new dihydrobenzofuran neolignan was isolated from the Actinidia valvata. Eleven known compounds were isolated form the Actinidia valvata. Compounds 1 –8 were isolated from Actinidia valvata for the first time. The compounds 1 –2 may be considered as chemotaxonomic markers of Actinidia valvata.